2017
DOI: 10.1038/ejcn.2017.130
|View full text |Cite
|
Sign up to set email alerts
|

Hot infusions and risk of colorectal cancer in Uruguay: a case–control study

Abstract: We found evidence of different significant inverse associations for tea, 'mate' and coffee intake and CRC risk. To our knowledge, this is the first epidemiologic study reporting inverse results on 'mate' intake and CRC, which are explained by a stronger association among women.European Journal of Clinical Nutrition advance online publication, 23 August 2017; doi:10.1038/ejcn.2017.130.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
5
0
3
Order By: Relevance
“…Results show a negative correlation between daily yerba mate intake and breast cancer [12][13]. In another study, high yerba mate intake had a significant inverse correlation with colorectal cancer onset [14].…”
Section: Introductionmentioning
confidence: 87%
“…Results show a negative correlation between daily yerba mate intake and breast cancer [12][13]. In another study, high yerba mate intake had a significant inverse correlation with colorectal cancer onset [14].…”
Section: Introductionmentioning
confidence: 87%
“…In previous studies, this infusion was identified as a risk factor for oral, esophageal, and laryngeal cancer (Loria, Barrios, & Zanetti, 2009;Ronco et al, 2004;Sewram, De Stéfani, Brennan, & Boffetta, 2003). In the first epidemiological study of its kind, Ronco et al (2017) found an inverse relation between mate consumption and CRC incidence rates, suggesting that mate is a protective factor for this cancer type. The aforementioned carcinogenicity found for other cancer types has been linked to the hot temperature at which mate is traditionally consumed rather than to chemical compounds inherent within mate (Ghassan Riachi & Bastos De Maria, 2017).…”
Section: Risk Factors For Crcmentioning
confidence: 99%
“…In 1990, the International Agency for Research on Cancer office of the WHO (IARC) classified series of publications that linked consumption with different types of cancer, mainly the oropharynx [17,18]. Since then, research has been carried out to demonstrated a link between the consumption of hot beverages and cancer, as well as an antimutagenic and protective effect of the yerba mate infusion [19][20][21]. On the other hand, there are some authors who claimed that polycyclic aromatic hydrocarbons (PAH) derived from the incomplete combustion of wood as contaminants present in the yerba mate leaf, are responsible for the association between the infusion and cancer, because of the presence of PAH as they are recognized carcinogenic agents [22].…”
Section: Mini Reviewmentioning
confidence: 99%